Distribution of Water Henna Plant Cultivation Farmers (Impatiens balsamina) in Jombang Regency Based on GIS - Ichsaul Chumamy; Dyah Ayu Sri Hartati; M Anshori Aris Widya (NEWTON: Networking and Information Technology, 2022)
Jombang is one of the regencies located in East Java Province which has an area of approximately 1,159.50 KM². Jombang Regency has a large area of agriculture and plantations. Most of the livelihoods of the people of Jombang Regency are farming. Jombang Regency has many areas of rice fields and plantations that can be excelled to support the economy of its people. One type of commodity that is in great demand in the community is water henna plants. Water henna plants are often found in Jombang Regency. There is little information about water henna plants in Jombang district, so not everyone knows their distribution. Therefore, an application is needed to provide information about the distribution of water henna cultivation farmers in Jombang Regency. GIS (Geographic Information System) is a computer information system that can provide specific geographic information of an area. This study aims to provide data and information about the distribution of water henna farmers in Jombang Regency.